2000
DOI: 10.1161/01.cir.101.5.524
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Coronary Smooth Muscle Cells and Adventitial Fibroblasts

Abstract: Coronary SMCs appeared to maintain highly differentiated phenotype in response to stimulation, whereas coronary adventitial fibroblasts demonstrated several characteristics that are essential during vascular repair. Coronary SMCs, however, were distinct from noncoronary medial cells, which displayed greater phenotypic heterogeneity and versatility in culture. We postulate that the mechanism of vascular repair may differ among vascular beds, pointing to the importance of coronary artery-specific investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 58 publications
2
58
1
Order By: Relevance
“…We and others recently reported that cultured porcine coronary artery SMCs maintain a high degree of differentiation in vitro, 9,23 contrary to what has been reported for rodent arterial SMCs. 18,24 In the present study, SMC marker expression was very similar in the populations of neointimal SMCs cultured after either stent or PTCA.…”
Section: Smc Marker Expression In Cultured Cellscontrasting
confidence: 56%
See 1 more Smart Citation
“…We and others recently reported that cultured porcine coronary artery SMCs maintain a high degree of differentiation in vitro, 9,23 contrary to what has been reported for rodent arterial SMCs. 18,24 In the present study, SMC marker expression was very similar in the populations of neointimal SMCs cultured after either stent or PTCA.…”
Section: Smc Marker Expression In Cultured Cellscontrasting
confidence: 56%
“…Moreover, it has been reported that porcine coronary SMCs behave differently in vitro from adventitial fibroblasts and from SMCs of elastic arteries. 23 All these data support, albeit indirectly, the SMC origin of intimal lesions.…”
Section: Smc Marker Expression In Cultured Cellsmentioning
confidence: 78%
“…The responses of porcine coronary SMCs to TGF-␤1 in vitro differ from those of rat arterial SMCs, 23 and coronary SMCs display distinct behavior from noncoronary SMCs in vitro, leading to the suggestion that repair mechanisms may differ between coronary and noncoronary vessels. 24 The stimulatory effect of TGF-␤1 on collagen synthesis by porcine SMCs in vitro is significantly less marked in cells cultured on collagen matrices than on monolayers. 25 This also appears to be true for porcine fibroblasts in vivo, 26 suggesting that the fibrogenic effects of TGF-␤1 on coronary SMCs in vivo, where cells are surrounded by basement membrane within a 3D collagen matrix, may differ from those observed in noncoronary SMC monolayers.…”
Section: Discussionmentioning
confidence: 98%
“…29 SMCs isolated by enzymatic digestion from the NM exhibit a spindle-shaped phenotype and grow in a hill-and-valley configuration, 29,42 similar to SMCs derived from the porcine aortic NM. 43,44 In contrast, SMCs obtained by tissue explantation are either spindle-shaped or rhomboid (flat, but more elongated than epithelioid rat SMCs); the luminal side of the media yields equal proportions of spindle-shaped and rhomboid SMCs, whereas the abluminal side yields a high proportion of rhomboid SMCs (Figure 1). 29 With these same techniques, IT induced 15 days after stent implantation gives rise to a high proportion of rhomboid SMCs.…”
Section: Establishment Of Distinct Smc Populationsmentioning
confidence: 99%